УЛЬТРАСТРУКТУРА ТКАНИН ПАРОДОНТА НАПРИКІНЦІ ДРУГОГО ТИЖНЯ ЕКСПЕРИМЕНТАЛЬНОГО ОПІОЇДНОГО ВПЛИВУ (World Science, 2019)
The following work is aimed at the study of submicroscopic disorganization in periodontal tissues with a two-week action of an opioid analgesic in an experiment. The aim was achieved by means of ultrastructural imaging of the cellular components of the mucous membrane of the gums and links of the hemomicrocirculatory bed. Ultrastructural preparations were prepared according to the conventional method. The conducted research provide a morphological basis to trace, at a more distant date, submicroscopic changes in soft periodontal tissues in dynamics against the background of a gradually increasing dose of opioid analgesic in the experiment.